The Pretreatment Neutrophil/Lymphocyte Ratio Is Associated with All-Cause Mortality in Black and White Patients with Non-metastatic Breast Cancer - Rimando, Joseph; Campbell, Jeff; Kim, Jae Hee; Tang, Shou-Ching; Kim, Sangmi (Frontiers in Oncology, 2016)
The pretreatment neutrophil/lymphocyte ratio (NLR), derived from differential white blood cell counts, has been previously associated with poor prognosis in breast cancer. Little data exists, however, concerning this association in black patients, who are known to have lower neutrophil counts than other racial groups. We conducted a retrospective cohort study of 236 black and 225 non-Hispanic white breast cancer patients treated at a single institution. Neutrophil and lymphocyte counts were obtained from electronic medical records. Univariate and multivariate Cox regression models were used to determine hazard ratios (HRs) and 95% confidence intervals (95% CIs) of all cause-mortality and breast cancer-specific mortality in relation to pretreatment NLR. Overall, there were no associations between an elevated pretreatment NLR (NLR ≥ 3.7) and all-cause or breast cancer-specific mortality. Among patients without metastasis at the time of diagnosis, an elevated pretreatment NLR was independently associated with all-cause mortality, with a multivariable HR of 2.31 (95% CI: 1.10-4.86). Black patients had significantly lower NLR values than white patients, but there was no evidence suggesting racial heterogeneity of the prognostic utility of NLR. Pretreatment NLR was an independent predictor of all-cause mortality but not breast cancer-specific mortality in non-metastatic breast cancer patients.